2010
DOI: 10.1007/s00216-010-3712-x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of triazines and their main transformation products in surface and urban wastewater by ultra-high-pressure liquid chromatography–tandem mass spectrometry

Abstract: This work describes the optimization, validation and application to real samples of an ultra-high-pressure liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method for the quantification and confirmation of 11 compounds (atrazine, simazine, terbuthylazine, terbumeton, terbutryn and their main transformation products) in surface and wastewater samples. Most of these analytes are included in the list of priority substances in the framework on European Water Policy. The application of this method to wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 35 publications
(32 reference statements)
4
27
1
1
Order By: Relevance
“…The results of the present study in EWW from Spain were in line with other studies, where triazines, carbendazim, thiabendazole, diazinon and/or imidacloprid were also identified (BarcoBonilla et al, 2013a(BarcoBonilla et al, , 2013bBenvenuto et al, 2010;Masia et al, 2013). The carbamate insecticide carbaryl was detected only in one EWW sample, but it was not investigated in other studies.…”
Section: Spainsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of the present study in EWW from Spain were in line with other studies, where triazines, carbendazim, thiabendazole, diazinon and/or imidacloprid were also identified (BarcoBonilla et al, 2013a(BarcoBonilla et al, , 2013bBenvenuto et al, 2010;Masia et al, 2013). The carbamate insecticide carbaryl was detected only in one EWW sample, but it was not investigated in other studies.…”
Section: Spainsupporting
confidence: 92%
“…Deethyl terbutylazine and deethyl terbumeton were detected in EWW (Benvenuto et al, 2010). The same compounds were identified in the present study and were the only ones identified in IWW and EWW.…”
Section: Benvenuto Et Al (2010) Analyzed Iww and Eww Samples For Trisupporting
confidence: 87%
See 3 more Smart Citations